Adaptive Strategies Used in Urban Houses to Overheating: A Systematic Review - Afolabi, Sakirat Abimbola; Adedire, Mokunfayo Funmilayo (Alanya Üniversitesi, 2023)
Recently, urban regions are experiencing prolonged heat exposure due to climate change and increased population expansion. Physiological, psychological and behavioural measures improve residents’ thermal comfort to solve the overheating issues generated by the scenario. However, adaptive strategies have not been clearly categorized based on the building construction process. This paper systematically reviews 101 documents published from 2013 to 2023, across 22 countries, with a focus on Nigeria. Using descriptive statistics and content analysis, we identify and categorize 52 adaptive strategies into four groups: urban design, effective building design, insulation, and occupants’ behaviour. These strategies are further classified according to their application in the building process stages: pre-design, design, construction, and post-construction. The study provides a full response to overheating in the building sector with efforts to reduce energy consumption rate and greenhouse gas emissions. The findings of the study contribute, significantly to improvement in occupants’ health care and well-being, as well as high productivity levels and socioeconomic benefits. Future research is therefore recommended in the efficiency of its implementation to develop innovative and cost-effective solutions in the construction industry towards sustainable urban development.